A flexible multi-objective task allocation method for major marine emergencies - Guo, Yu; Mao, Jiahui; Zhang, Haidong; Li, Jichao; Yang, Qingqing; Yang, Kewei (Ocean engineering, 2024)
The boom in the maritime economy has led to an increase in the frequency of major marine emergencies, and it is critical for decision-makers to develop a well-planned task-allocation scheme. Compared to ordinary marine emergencies, major marine emergencies (MME) are characterized by multiple tasks, evolving scenarios, and difficulties in terms of adjustment. This paper introduces flexibility theory into marine emergency decision-making by proposing a novel framework called the two-phase flexible task-allocation scheme generation (TFTASG). We first developed a multi-objective programming model of the TFTASG in two phases: three objectives of responding to MME within a critical time and the maximization of the subject’s enthusiasm and task completion efficiency were designed in the first phase, and different objectives are formulated according to different task types; the objective of flexibility maximization was constructed in the second phase. Then, to solve the combinatorial explosion problem and generate timely solutions, the improved differential evolution algorithm was proposed according to the characteristics of the TFTASG. Finally, a real-world case was carried out to demonstrate the effectiveness of our model. The results show that our proposed flexible task-allocation scheme can achieve fast adjustment at low cost and that the TFTASG can provide decision-makers with scientific decision support. •A novel decision-making framework called TFTASG is proposed to generate a flexible task allocation scheme.•A multi-objective programming model in two phases is built for major marine emergencies to allocate multiple tasks.•An improved differential evolution algorithm was proposed to solve TFTASG.•The effectiveness of TFTASG is proved using a real case of major maritime emergency.